Biological characterization of Bothrops marajoensis snake venom - Cavalcante, Walter LG (Library Publishing Media, 2011)
This study describes the effects of Bothrops marajoensis venom (Marajó lancehead) on isolated neuromuscular preparations of chick biventer cervicis (CBC) and mouse phrenic nerve-diaphragm (PND). At low concentrations (1µg/ml for CBC and 5µg/ml for PND), the venom exhibited a neuromuscular blocking without any damaging effect on the muscle integrity. At higher concentration (20μg/ml for PND), together with the neuromuscular blockade, there was a moderate myonecrosis. The results show differences between mammalian and avian preparations in response to venom concentration; the avian preparation was more sensitive to venom neurotoxic effect than the mammalian preparation. The possible presynaptic mechanism underlying the neuromuscular blocking effect was reinforced by the observed increase in MEPPs at the same time (at 15min) when the facilitation of twitch tension occurred. These results indicate that the B. marajoensis venom produced neuromuscular blockade, which appeared to be presynaptic at low concentrations with a postsynaptic component at high concentrations, leading to muscle oedema. These observations demand the fractionation of the crude venom and characterization of its active components for a better understanding of its biological dynamics.